Polishing composition for fluorophosphate glass, and polishing method using the polishing composition for fluorophosphate glass
A silica-based abrasive composition with specific components and pH range enhances polishing rates and surface smoothness for fluorophosphate glass, addressing the limitations of silica-based abrasives and cerium oxide depletion.
Patent Information
- Application Number
- JP2020210465
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-18
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Silica-based abrasives have low polishing rates compared to cerium oxide-based abrasives, and there is a need for a cost-effective alternative to cerium oxide due to resource depletion concerns, while fluorophosphate glass is difficult to polish due to high abrasion and thermal expansion, leading to processing accuracy issues and surface scratches.
An abrasive composition for fluorophosphate glass comprising silica, a water-soluble polymer compound, an acid and/or its salt, and water, with specific pH and particle size ranges, is developed to improve polishing rates and surface smoothness.
The composition achieves improved polishing rates and reduces surface clouding and scratches, providing a cost-effective alternative to cerium oxide-based abrasives for polishing fluorophosphate glass.
Smart Images

Figure 0007619796000001 
Figure 0007619796000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an abrasive composition for fluorophosphate glass and a polishing method using the abrasive composition for fluorophosphate glass. More specifically, the present invention relates to an abrasive composition for fluorophosphate glass for polishing fluorophosphate glass that is suitable for use in the lenses of digital cameras and the lenses of cameras built into smartphones, and a polishing method using the abrasive composition for fluorophosphate glass. [Background technology]
[0002] Conventionally, solid-state imaging devices used in digital cameras and cameras built into smartphones have spectral sensitivity ranging from the visible region to the near-infrared region around 1200 nm. Therefore, since it is difficult to obtain good color reproduction when used as is, the visibility is corrected by using near-infrared cut filter glass formed by adding a specific substance with infrared absorbing properties.
[0003] Optical glass made by adding copper oxide to fluorophosphate glass has been developed and used as a near-infrared cut filter glass, because it has the property of selectively absorbing infrared rays with wavelengths in the near-infrared region and has high weather resistance. Ordinary glass mainly contains silica or silica and alumina components, but fluorophosphate glass contains virtually no silica component and is composed of components optimized to absorb infrared rays with wavelengths in the near-infrared region.
[0004] To explain in more detail, fluorophosphate glass generally contains phosphorus ions (P 5+ ) is 15-50%, aluminum ion (Al 3+ ) is 5-30%, calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ) and strontium ion (Sr 2+ ) and barium ion (Ba 2+ ) and zinc ions (Zn 2+) with a total content of 10 to 40% of one or more selected from lithium ion (Li + ) and sodium ions (Na + ) and potassium ion (K + ) in a total amount of 5 to 30%, and copper ions (Cu 2+ ) is 0-20%, and anion % is fluoride ion (F - ) 10-50%, and oxygen ions (O 2- ) is contained within the range of 50 to 90%.
[0005] Here, "cation %" and "anion %" are defined as the units shown below. That is, when the constituent components of fluorophosphate glass are divided into cationic components and anionic components, and the total content of all cationic components contained in the fluorophosphate glass is taken as 100 mol%, the unit expressing the content of each cationic component as a molar percentage corresponds to "cation %". On the other hand, when the total content of all anionic components contained in the fluorophosphate glass is taken as 100 mol%, the unit expressing the content of each anionic component as a molar percentage corresponds to "anion %".
[0006] The production of near-infrared cut filter glass is mainly composed of a melting process in which glass raw materials such as tripolyphosphate powder, orthophosphoric acid, or other phosphoric acid raw materials, fluoride raw materials, and copper oxide raw materials are melted at a temperature of 600° C. to 1000° C. for 2 to 80 hours, a fining process to remove bubbles in the glass, a stirring process to homogenize the glass, and a forming process to flow and form the molten glass. Methods in which each of the above steps is performed using one crucible furnace, or a method in which each step is performed using a continuous furnace having multiple different tanks connected to each other by transport pipes, are known.
[0007] The fluorophosphate glass produced in this manner exhibits properties such as a high degree of abrasion resistance and a high coefficient of thermal expansion compared to the properties of other general optical glasses, which makes polishing of such fluorophosphate glass difficult.
[0008] Such glass materials that are difficult to polish are called "refractory glass materials" and require careful handling during the processing steps in the glass manufacturing process. That is, the glass materials are soft and the surface is easily scratched, or are too hard and difficult to process. In addition to the above-mentioned fluorophosphate glass, for example, niobium phosphate-containing high refractive index, high dispersion glass and lanthanum borate-containing high refractive index, low dispersion glass are known.
[0009] In particular, when the glass material to be polished is highly abrasive, the processing accuracy decreases and scratches caused during polishing tend to remain on the glass surface. Therefore, when polishing fluorophosphate glass, special care must be taken in selecting the abrasive and setting the polishing conditions compared to general optical glass.
[0010] Therefore, a method of using a cerium oxide-based abrasive containing cerium oxide as a main component has been conventionally used to polish fluorophosphate glass (see Patent Documents 1 and 2). However, cerium is a rare metal, and there have been concerns about its supply due to resource depletion and rising cerium prices. For this reason, there has been a demand for an alternative to silica-based abrasives containing silica as a main component, which is inexpensive and can be supplied stably. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2013-141737 A [Patent Document 2] International Publication No. 2017 / 102826 Summary of the Invention [Problem to be solved by the invention]
[0012] However, silica-based abrasives have a problem in that they have a lower polishing rate than the above-mentioned cerium oxide-based abrasives, and an improvement in this polishing rate has been desired.
[0013] In view of the above-mentioned circumstances, an object of the present invention is to provide an abrasive composition for fluorophosphates glass which has a high removal rate and can be used to polish fluorophosphates glass as an alternative to cerium oxide-based abrasives, and a polishing method using the abrasive composition for fluorophosphates glass. [Means for solving the problem]
[0014] In order to solve the above-mentioned problems, the inventors of the present application have conducted extensive research into the issue of silica-based abrasives, which is that the removal rate is low. As a result, they have discovered an abrasive composition for fluorophosphates glass that improves the removal rate of silica-based abrasives and is capable of finishing the glass surface of fluorophosphates glass to an excellent smoothness without causing cloudiness or scratches on the glass surface after polishing, and a polishing method using said abrasive composition for fluorophosphates glass, and have completed the present invention described below.
[0015] [1] A composition comprising silica, a water-soluble polymer compound, an acid and / or a salt thereof, and water; the water-soluble polymer compound is a polymer having a structural unit derived from a polysaccharide and / or an unsaturated amide, An abrasive composition for fluorophosphate glass, having a pH (25°C) value in the range of 1.0 to 9.0.
[0016] [2] The abrasive composition for fluorophosphates glass according to [1], wherein the silica is colloidal silica and has an average particle size (D50) in the range of 10 nm to 200 nm.
[0018] [ 3 The acid and / or its salt is an inorganic acid and / or its salt. or [ 2 ] An abrasive composition for fluorophosphate glass according to the present invention.
[0019] [ 4 The acid and / or its salt is an organic acid and / or its salt. or [ 2] The abrasive composition for fluorophosphate glass described above.
[0020] [ 5The polymer having a structural unit derived from an unsaturated amide is a copolymer containing a structural unit derived from (meth)acrylamide and / or an N-substituted (meth)acrylamide and a structural unit derived from (meth)acrylic acid and / or a salt thereof. 1 ] An abrasive composition for fluorophosphate glass according to the present invention.
[0021] [ 6 The inorganic acid and / or its salt is a phosphorus-containing inorganic acid and / or its salt. 3 ] An abrasive composition for fluorophosphate glass according to the present invention.
[0022] [ 7 The organic acid and / or its salt is a chelating compound. 4 ] An abrasive composition for fluorophosphate glass according to the present invention.
[0023] [ 8 The chelating compound is at least one selected from the group consisting of dicarboxylic acids and / or salts thereof, tricarboxylic acids and / or salts thereof, polyaminocarboxylic acid compounds, and phosphonic acid compounds. 7 ] An abrasive composition for fluorophosphate glass according to the present invention.
[0024] [ 9 ] The above [1] ~ [ 8 13. A polishing method using an abrasive composition for fluorophosphates glass, comprising polishing fluorophosphates glass using the abrasive composition for fluorophosphates glass described in any one of claims 1 to 12. Effect of the Invention
[0025] The polishing composition for fluorophosphate glass of the present invention contains silica, a water-soluble polymeric compound, an acid and / or its salt, and water. By polishing fluorophosphate glass with the composition, the polishing rate can be improved and a smooth glass surface free of cloudiness or scratches can be obtained after polishing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described below in detail with reference to the preferred embodiments. The present invention is not limited to the following embodiments, and changes, modifications, and improvements can be made without departing from the scope of the present invention.
[0027] 1. Polishing composition for fluorophosphate glass The polishing compound composition for fluorophosphate glass of this embodiment (hereinafter simply referred to as "polishing compound composition") contains silica, a water-soluble polymeric compound, an acid and / or its salt, and water.
[0028] 1.1 Silica The silica contained as one component of the polishing agent composition of this embodiment can be fumed silica, wet process silica, colloidal silica, etc., and colloidal silica is particularly suitable. Furthermore, the colloidal silica preferably has an average particle size (D50) in the range of 10 nm to 200 nm, and more preferably has an average particle size (D50) in the range of 20 nm to 150 nm.
[0029] By making the average particle size (D50) of colloidal silica 10 nm or more, the aggregation of colloidal silica is less likely to occur, and the storage stability can be improved. On the other hand, by making the average particle size (D50) of colloidal silica 200 nm or less, the smoothness of the glass surface after polishing can be improved, and the occurrence of cloudiness and scratches can be suppressed. Here, the average particle size (D50) of colloidal silica is calculated by analysis based on the observation results by a transmission electron microscope (TEM) (details will be described later).
[0030] Colloidal silica can be of any known shape, such as spherical or confetti-shaped (particulate with protrusions on the surface), and the primary particles are monodispersed in water to form a colloid.
[0031] The colloidal silica used can be manufactured by a conventionally known manufacturing method, for example, the water glass method, which uses alkali metal silicate such as sodium silicate or potassium silicate as raw material, and grows colloidal silica particles by condensing the raw material in an aqueous solution; the alkoxysilane method, which uses tetraalkoxysilane such as tetraethoxysilane as raw material, and grows colloidal silica particles by condensing the raw material with an acid or alkali in a solvent containing a water-soluble organic solvent such as alcohol; or the method of synthesizing colloidal silica by reacting metal silicon with water in the presence of an alkali catalyst.Note that the water glass method can be used preferably in terms of manufacturing cost.The colloidal silica that is the material used in the abrasive composition for fluorophosphate glass of the present embodiment can be manufactured by appropriately using these synthesis methods.
[0032] In the polishing compound of this embodiment, the concentration (content) of colloidal silica contained in the polishing compound is preferably in the range of 1 mass % to 50 mass %, and more preferably in the range of 2 mass % to 45 mass %, from the viewpoints of ensuring a stable dispersion state of the abrasive particles and of economic efficiency.
[0033] By setting the concentration of colloidal silica to 1% by mass or more, the polishing rate can be improved, while by setting the concentration of colloidal silica to 50% by mass or less, it is advantageous in terms of economy and has the advantage that aggregation and gelation are less likely to occur when further adding and blending abrasives other than colloidal silica and other compounding agents.
[0034] 1.2 Water-soluble polymer compounds The water-soluble polymer compound contained as one component of the polishing compound composition of this embodiment may be a polysaccharide, an acrylic acid polymer, a methacrylic acid polymer, a polymer having a structural unit derived from an unsaturated amide, or the like, and it is preferable to use a polymer having a structural unit derived from a polysaccharide or an unsaturated amide.
[0035] Furthermore, in the polishing compound of this embodiment, the concentration of the water-soluble polymer compound contained in the polishing compound is preferably in the range of 0.0001% by mass to 10.0% by mass, and more preferably in the range of 0.001% by mass to 5.0% by mass.
[0036] By setting the concentration of the water-soluble polymer compound to 0.0001% by mass or more, clouding and scratches on the substrate surface after polishing can be suppressed. By setting the concentration of the water-soluble polymer compound to 10.0% by mass or less, not only is it advantageous in terms of economy, but also it is possible to prevent the polishing compound composition for fluorophosphate glass from becoming highly viscous.
[0037] Furthermore, examples of polysaccharides used as the water-soluble polymer compound include alginic acid, alginic acid esters, pectinic acid, carboxymethyl cellulose, agar, xanthan gum, chitosan, methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, and hydroxyethyl cellulose.
[0038] On the other hand, as the polymer having a structural unit derived from an unsaturated amide used as the water-soluble polymer compound, a copolymer containing a structural unit derived from an unsaturated amide and a structural unit derived from a carboxyl group-containing vinyl monomer is preferable, and more preferable examples include a copolymer containing a structural unit derived from (meth)acrylamide and / or an N-substituted (meth)acrylamide and a structural unit derived from (meth)acrylic acid and / or a salt thereof.
[0039] Here, (meth)acrylamide refers to acrylamide and / or methacrylamide, and (meth)acrylic acid refers to acrylic acid and / or methacrylic acid. Hereinafter, in this specification, (meth) has the same meaning as above.
[0040] Furthermore, the N-substituted (meth)acrylamide is represented by the following formula (1): CH2=C(R 1 )-CONR 2 (R 3) ···(1) It is a compound that can be generally represented as: Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 3 represents a straight or branched alkyl group having 1 to 4 carbon atoms.
[0041] R shown in the above formula (1) 2 or R 3 Examples of the linear or branched alkyl group having 1 to 4 carbon atoms in the formula (I) include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, and a t-butyl group, while specific examples of the N-substituted (meth)acrylamide include N,N-dimethyl(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, Nn-propyl(meth)acrylamide, Ni-propyl(meth)acrylamide, Nn-butyl(meth)acrylamide, Ni-butyl(meth)acrylamide, Ns-butyl(meth)acrylamide, and Nt-butyl(meth)acrylamide.
[0042] Examples of the carboxyl group-containing vinyl monomer include monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and (meth)acrylic carboxylic acid, dicarboxylic acids such as itaconic acid, maleic acid, and fumaric acid, and alkali metal salts such as sodium salts and potassium salts of these various organic acids, and ammonium salts, etc. In particular, those using (meth)acrylic acid or itaconic acid are preferred.
[0043] Furthermore, the ratio of the constituent units derived from the unsaturated amide and the constituent units derived from the carboxyl group-containing vinyl monomer in the copolymer is preferably in the range of 99:1 to 10:90 in terms of molar ratio, and more preferably in the range of 98:2 to 10:90.
[0044] Furthermore, vinyl monomers other than those mentioned above can also be suitably used. For example, examples of anionic vinyl monomers include organic sulfonic acids such as vinyl sulfonic acid, styrene sulfonic acid, and 2-acrylamido-2-methylpropanesulfonic acid, and alkali metal salts such as sodium salts and potassium salts of these various organic acids, and ammonium salts.
[0045] Further, examples of nonionic vinyl monomers include carboxyl group-containing vinyl monomers or alkyl esters of the above-mentioned anionic vinyl monomers, acrylonitrile, styrene, divinylbenzene, vinyl acetate, methyl vinyl ether, and N-vinylpyrrolidone.
[0046] In addition, in a method for producing a carboxyl group-containing poly(meth)acrylamide obtained by copolymerizing (meth)acrylamide and / or N-substituted (meth)acrylamide, a carboxyl group-containing vinyl monomer, and, if necessary, a vinyl monomer other than those mentioned above, well-known means can be adopted.
[0047] As an example, the above-mentioned various monomers and water are charged into a specified reaction vessel, a radical polymerization initiator is added, and the mixture is heated with stirring to obtain the desired carboxyl group-containing poly(meth)acrylamide.
[0048] In this case, as the radical polymerization initiator, a usual radical polymerization initiator such as a persulfate such as potassium persulfate or ammonium persulfate, or a redox-based polymerization initiator in the form of a combination of these with a reducing agent such as sodium hydrogen sulfite can be used. Furthermore, as the radical polymerization initiator, an azo-based initiator may be used. The amount of such radical polymerization initiator used can be in the range of 0.05% by mass to 2% by mass of the sum of the total amount of vinyl monomers used.
[0049] The weight-average molecular weight of the polymer having a structural unit derived from an unsaturated amide is usually about 1,000 to 10,000,000, preferably 10,000 to 5,000,000, and more preferably 100,000 to 3,000,000. The weight-average molecular weight is a value measured using GPC (gel permeation chromatography) and converted into standard polystyrene.
[0050] 1.3 Acids and / or their salts The acid and / or its salt contained as one component of the polishing compound composition of the present embodiment is an inorganic acid and / or its salt, or an organic acid and / or its salt. Note that the acid and / or its salt may be a combination of an inorganic acid and / or its salt and an organic acid and / or its salt.
[0051] Examples of inorganic acids and / or salts thereof include sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, phosphonic acid, phosphinic acid, tripolyphosphoric acid, pyrophosphoric acid, and / or salts thereof, etc. More preferably, phosphorus-containing inorganic acids and / or salts thereof can be used, and particularly preferably, phosphoric acid, phosphonic acid, phosphinic acid, tripolyphosphoric acid, pyrophosphoric acid, and / or salts thereof can be used.
[0052] On the other hand, as the organic acid and / or its salt, at least one selected from the group consisting of monocarboxylic acid and / or its salt, dicarboxylic acid and / or its salt, tricarboxylic acid and / or its salt, polyaminocarboxylic acid compound, and phosphonic acid compound can be used. More preferably, a chelating compound can be used.
[0053] As the chelating compound, dicarboxylic acid and / or its salt, tricarboxylic acid and / or its salt, polyaminocarboxylic acid compound, phosphonic acid compound, etc. As the dicarboxylic acid and / or its salt, malic acid, malonic acid, maleic acid, tartaric acid and / or its salt, etc. can be used, and as the tricarboxylic acid and / or its salt, citric acid and / or its salt, etc. can be used.
[0054] On the other hand, as the polyaminocarboxylic acid compound, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, nitrilotriacetic acid, and their ammonium salts, amine salts, sodium salts, potassium salts, etc. can be used. As the phosphonic acid compound, diethylenetriaminepentamethylenephosphonic acid, phosphonohydroxyacetic acid, hydroxyethyldimethylenephosphonic acid, aminotrismethylenephosphonic acid, hydroxyethanephosphonic acid, ethylenediaminetetramethylenephosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, and their ammonium salts, amine salts, sodium salts, potassium salts, etc. can be used. Among the above chelating compounds, tricarboxylic acid and / or its salt, and polyaminocarboxylic acid compound, etc. can be more preferably used.
[0055] The content of the acid and / or its salt in the polishing compound for fluorophosphate glass is determined from the viewpoint of adjusting the pH value (25°C) of the polishing compound for fluorophosphate glass to a set value, and is preferably 0.01% by mass to 10% by mass, more preferably 0.05% by mass to 8% by mass. By making it 0.01% by mass or more, the polishing speed can be improved. By making it 10% by mass or less, clouding of the substrate surface after polishing can be suppressed.
[0056] 1.4 Water The water contained as one component of the polishing compound composition of the present embodiment is used as a medium for dispersing other components of the polishing compound composition, and preferably used is pure water, ultrapure water, distilled water, etc. In order to smoothly disperse other components of the polishing compound composition, the polishing compound composition may contain an appropriate amount of an organic medium such as alcohol.
[0057] 1.5 Physical properties of the abrasive composition The pH value (25°C) of the polishing compound of this embodiment is in the range of 1.0 to 9.0, preferably in the range of 2.0 to 8.0. If the pH value (25°C) is less than 1.0, there is a concern that the cloudiness of the substrate surface after the polishing step may worsen, and if the pH value (25°C) is more than 9.0, there is a concern that the polishing rate may decrease. Here, the pH value (25°C) indicates the pH value at 25°C.
[0058] 2. How to polish fluorophosphate glass When using the polishing agent composition of this embodiment to polish fluorophosphate glass, various polishing methods well known in the art can be appropriately selected.For example, a predetermined amount of the polishing agent composition is put into a supply container installed in a polishing machine.The polishing agent composition is dropped and supplied from the supply container through a nozzle or tube to the polishing pad attached on the platen of the polishing machine, and the platen is rotated at a predetermined rotation speed while pressing the polishing surface of the object to be polished against the polishing pad, thereby polishing the polishing surface of the object to be polished.
[0059] The polishing pad may be made of a material commonly used in polishing, such as nonwoven fabric, polyurethane foam, porous resin, and nonporous resin. Furthermore, in order to facilitate the supply of the polishing agent composition to the polishing pad or to allow a certain amount of the polishing agent composition to remain on the polishing pad, the pad surface of the polishing pad may be provided with various grooves, such as a lattice-like, concentric-circular, or spiral-like groove. EXAMPLES
[0060] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples. In addition to the following examples, various modifications and improvements can be made to the present invention based on the knowledge of those skilled in the art, as long as they do not deviate from the gist of the present invention.
[0061] As shown below, Example 1 ,2,4 ~10 , Reference example 1The experimental examples of Comparative Examples 1 to 4 are the results of predetermined polishing tests carried out using a polishing agent composition for polishing fluorophosphate glass (composition for polishing fluorophosphate glass) containing the materials and additive amounts shown in Table 1. Furthermore, the results of the polishing tests are shown in Table 2.
[0062] In Tables 1 and 2, "AM" stands for acrylamide, "MAA" for methacrylic acid, "AA" for acrylic acid, "EDTA2N" for diammonium ethylenediaminetetraacetate, "EDTA3K" for tripotassium ethylenediaminetetraacetate, and "citric acid 2N" for diammonium hydrogen citrate. MW is the abbreviation for weight average molecular weight.
[0063] (1) Synthesis of water-soluble polymer compounds Example 1 ,2,4 ~10 , Reference example 1 The details of the synthesis procedures for the water-soluble polymer compounds used in Comparative Examples 1 to 4 are shown below.
[0064] (Synthesis Example 1) In a four-neck flask equipped with a thermometer, a reflux condenser, and a nitrogen inlet tube, 100 parts by mass of acrylamide (95 mol% relative to the total molar sum of vinyl monomers), 6.3 parts by mass of methacrylic acid (5 mol%), 5.3 parts by mass of isopropyl alcohol, and 400 parts by mass of ion-exchanged water were charged, and oxygen in the reaction system was removed by passing nitrogen gas through it. The temperature in the reaction system was adjusted to 40°C, and 0.3 parts by mass of ammonium persulfate and 0.2 parts by mass of sodium hydrogen sulfite were added as polymerization initiators under stirring. The start of polymerization was confirmed by heat generation, and after the reaction liquid temperature reached 90°C, the temperature was maintained for 2 hours. After the polymerization was completed, 5.5 parts by mass of 48% aqueous sodium hydroxide solution and 11 parts by mass of ion-exchanged water were added to obtain a carboxyl group-containing polyacrylamide aqueous solution with a pH value (25°C) of 7.5 and a polymer concentration of 20%. The composition of the obtained water-soluble polymer compound was acrylamide / methacrylic acid = 95 / 5 (mol%), and the weight average molecular weight was 1,400,000.
[0065] (Synthesis Example 2) A four-neck flask equipped with a thermometer, a reflux condenser, and a nitrogen inlet tube was charged with 100 parts by mass of acrylamide (95 mol% relative to the total molar sum of vinyl monomers), 5.3 parts by mass of acrylic acid (5 mol%), 5.3 parts by mass of isopropyl alcohol, and 400 parts by mass of ion-exchanged water, and oxygen in the reaction system was removed by passing nitrogen gas through it. The reaction system was adjusted to 40°C, and 0.3 parts by mass of ammonium persulfate and 0.2 parts by mass of sodium hydrogen sulfite were added as polymerization initiators under stirring. The start of polymerization was confirmed by heat generation, and after the reaction liquid temperature reached 90°C, the temperature was maintained for 2 hours. After the polymerization was completed, 5.5 parts by mass of 48% aqueous sodium hydroxide solution and 11 parts by mass of ion-exchanged water were added to obtain a carboxyl group-containing polyacrylamide aqueous solution with a pH value (25°C) of 7.5 and a polymer concentration of 20%. The composition of the obtained water-soluble polymer compound was acrylamide / acrylic acid = 95 / 5 (mol%), and the weight average molecular weight was 900,000.
[0066] (Synthesis Example 3) Homopolymerization of acrylic acid was carried out using acrylic acid instead of the acrylamide used in Synthesis Example 2. The resulting water-soluble polymer compound was an acrylic acid homopolymer, and had a weight-average molecular weight of 12,000.
[0067] (2) Preparation of abrasive composition (Polishing composition of Example 1) A commercially available colloidal silica slurry (average particle size (D50) = 40 nm, silica concentration = 40 mass%), the water-soluble polymer compound synthesized in Synthesis Example 1, and diammonium ethylenediaminetetraacetate (EDTA2N) were added while diluting with pure water to the concentrations shown in Table 1, and the mixture was stirred and mixed to homogenize, and used as the polishing compound composition of Example 1 in the polishing test.
[0068] (Polishing composition of Example 2) The water-soluble polymer compound synthesized in Synthesis Example 2 was used in place of the water-soluble polymer compound in Synthesis Example 1 used in the preparation of the polishing compound of Example 1. The other conditions were the same as in Example 1, and the polishing compound of Example 2 was used in the polishing test.
[0069] ( reference example 1 (Abrasive composition of In place of the water-soluble polymer compound of Synthesis Example 1 used in the preparation of the polishing compound of Example 1, the water-soluble polymer compound synthesized in Synthesis Example 3 was used. The other conditions were the same as in Example 1, reference example 1 The polishing composition was used in a polishing test.
[0070] (Polishing composition of Example 4) Propylene glycol alginate was used in place of the water-soluble polymer compound of Synthesis Example 1 used in the preparation of the polishing composition of Example 1. Other conditions were the same as in Example 1, and the polishing composition of Example 4 was used in the polishing test.
[0071] (Polishing composition of Example 5) A colloidal silica slurry having an average particle size (D50) of 110 nm and a silica concentration of 40 mass% was used instead of the commercially available colloidal silica slurry (average particle size (D50) of 40 nm and silica concentration of 40 mass%) used in the preparation of the polishing composition of Example 1. The other conditions were the same as those of Example 1, and the composition was used in the polishing test as the polishing composition of Example 5.
[0072] (Polishing composition of Example 6) Diammonium hydrogen citrate (citric acid 2N) was used instead of diammonium ethylenediaminetetraacetate (EDTA2N) used in the preparation of the polishing compound of Example 1. The other conditions were the same as in Example 1, and the polishing compound of Example 6 was used in the polishing test.
[0073] (Polishing composition of Example 7) The concentration of the water-soluble polymer compound used in the preparation of the polishing compound of Example 1 was changed to 1.5 mass %. Other conditions were the same as in Example 1, and the polishing compound of Example 7 was used in the polishing test.
[0074] (Polishing composition of Example 8) Instead of diammonium ethylenediaminetetraacetate (EDTA2N) used in the preparation of the polishing compound of Example 1, phosphoric acid was used at the concentration (concentration at which the pH value (25°C) was 1.4) shown in Table 1. The other conditions were the same as in Example 1, and the polishing compound of Example 8 was used in the polishing test.
[0075] (Polishing composition of Example 9) The concentration of diammonium ethylenediaminetetraacetate (EDTA2N) used in the preparation of the polishing composition of Example 1 was changed to the concentration (concentration at which the pH value (25°C) was 8.5) shown in Table 1. Other conditions were the same as in Example 1, and the polishing composition of Example 9 was used in the polishing test.
[0076] (Polishing composition of Example 10) The concentration of phosphoric acid used in the preparation of the polishing compound of Example 8 was changed to the concentration (concentration at which the pH value (25°C) was 2.5) shown in Table 1. Other conditions were the same as in Example 8, and the polishing compound of Example 10 was used in the polishing test.
[0077] (Polishing composition of Comparative Example 1) A commercially available cerium oxide slurry (average particle size = 300 nm, solid concentration = 20 mass %) was diluted with pure water to the concentration shown in Table 1, and used as the polishing compound composition of Comparative Example 1 in the polishing test.
[0078] (Polishing composition of Comparative Example 2) A commercially available colloidal silica slurry (average particle size (D50) = 40 nm, silica concentration = 40 mass%) and diammonium ethylenediaminetetraacetate (EDTA2N) were added while diluting with pure water to the concentrations shown in Table 1, and the mixture was stirred and mixed to homogenize. This was used in the polishing test as the polishing compound composition of Comparative Example 2.
[0079] (Polishing composition of Comparative Example 3) The phosphoric acid used in the preparation of the polishing compound of Example 8 was replaced with sulfuric acid, and the concentration (concentration at which the pH value (25°C) is 0.5) shown in Table 1 was used. Other conditions were the same as in Example 8, and the polishing compound of Comparative Example 3 was used in the polishing test.
[0080] (Polishing composition of Comparative Example 4) The diammonium ethylenediaminetetraacetate (EDTA2N) used in the preparation of the polishing compound of Example 9 was replaced with tripotassium ethylenediaminetetraacetate (EDTA3K) so as to have the concentration (concentration at which the pH value (25°C) becomes 9.5) shown in Table 1. The other conditions were the same as those of Example 9, and the polishing compound of Comparative Example 4 was used in the polishing test.
[0081] [Table 1]
[0082] [Table 2]
[0083] (Colloidal silica particle size) The particle size (Heywood diameter) of colloidal silica was measured as the Heywood diameter (diameter equivalent to a circle with a projected area) by taking a photograph of a field of view at a magnification of 100,000 times using a transmission electron microscope (TEM) (JEOL Ltd., JEM2000FX (200kV)) and analyzing the photograph using analysis software (Mountec Co., Ltd., Mac-View Ver 4.0). The average particle size of colloidal silica was determined by analyzing the diameters of approximately 2,000 colloidal silica particles using the method described above, and calculating the particle size at which the cumulative particle size distribution (accumulated volume basis) from the small particle size side is 50% using the above analysis software (Mountec Co., Ltd., Mac-View Ver 4.0), which is the average particle size (D50).
[0084] (polishing conditions) Example 1 ,2,4 ~10 , Reference example 1A polishing test using a polishing device was carried out for the polishing compound compositions of Comparative Examples 1 to 4. The polishing conditions for the polishing test were as follows. Polishing machine: Double-sided polishing machine (SPEED FAM 6B-5P-II) Substrate: Fluorophosphate glass substrate x 3 (76mm x 76mm square, thickness 0.9mm) Polishing pad: 2900W (suede: with XY grooves) Plate rotation speed: 50 rpm Processing pressure: 63g / cm 2 Processing time: 20min Abrasive composition supply rate: 200 ml / min (circulation method)
[0085] (Method of measuring polishing rate) The thickness of the substrate before and after polishing was measured using a micrometer (manufactured by Mitutoyo Corporation, measurement accuracy: 1 μm), and the polishing rate (μm / min) was measured. , Reference example 1 For the polishing compound compositions of the comparative examples and the like, three substrates were polished simultaneously, and the removal rate shown is the average value for the three substrates.
[0086] (Method for evaluating the haze on the substrate surface after polishing) The cloudiness of the substrate surface after polishing was judged visually by shining the light of a focusing lamp (ECO LIGHT 30,000 Lux, manufactured by Nagata Seisakusho Co., Ltd.) on the substrate surface and observing the reflected light based on the following evaluation conditions. Note that the judgment shows the overall judgment of three substrates polished at the same time. ·Fog evaluation conditions 〇: No cloudiness △: Partly cloudy ×: Cloudy all over
[0087] (Method for evaluating scratches on substrate surface after polishing) An ultra-fine defect high-speed visualization macro inspection device (Wacom Electronics Co., Ltd., W-SCOPE WUV) was used to evaluate scratches on the substrate surface after polishing. Among the concave defects on the substrate surface, scratches are defined as those with a long / short ratio of "5 or more:1" and a width of 5μm or more. The judgment is based on the average value per surface for a total of six surfaces of three substrates polished at the same time. · Evaluation conditions for scratches on the substrate surface 〇: No scratches (0 scratches / substrate surface) △: Slightly scratched (1 to 4 per board surface) ×: Many scratches (5 or more per board surface)
[0088] (Consideration) Compared with the polishing compound using cerium oxide abrasive grains in Comparative Example 1, the polishing compound using colloidal silica abrasive grains in Comparative Example 2 slightly improved the haze on the substrate surface (fluorophosphate glass surface) after polishing, but the polishing rate was low and scratches on the substrate surface were not improved. On the other hand, Example 1, in which a water-soluble polymer compound was added to the polishing compound of Comparative Example 2, improved the polishing rate, improved the haze, and improved the scratches compared to Comparative Example 2. That is, the addition of a water-soluble polymer compound to the polishing compound composition improved the haze and improved the scratches.
[0089] Example 2 , 4 and Reference Example 1 The polishing composition of Example 2 is an example in which the type of water-soluble polymer compound is changed compared to the preparation of the polishing composition of Example 1. The polishing composition of Example 5 is an example in which colloidal silica abrasive grains having a different average particle size (D50) are used compared to the preparation of the polishing composition of Example 1. On the other hand, the polishing composition of Example 6 is an example in which the acid and / or its salt in the preparation of the polishing composition of Example 1 is changed from 2N EDTA to 2N citric acid.
[0090] The polishing composition of Example 7 is an example in which, compared with the preparation of the polishing composition of Example 1, the amount of the water-soluble polymer compound added was changed.
[0091] Comparing the polishing compositions of Examples 8 and 10 with the polishing composition of Comparative Example 3, it can be seen that the pH value (25°C) of the polishing composition is 1.0 or higher, thereby improving the cloudiness and scratches on the surface of the fluorophosphate glass after polishing.
[0092] In addition, a comparison between the polishing composition of Example 9 and the polishing composition of Comparative Example 4 shows that the pH value (25°C) of the polishing composition is 9.0 or less, thereby improving the cloudiness and scratches on the substrate surface after polishing.
[0093] From the above, it has become clear that by using the polishing agent composition of the present invention to polish fluorophosphate glass, the polishing rate is improved and the occurrence of clouding and scratches on the surface of the fluorophosphate glass after polishing is suppressed. [Industrial Applicability]
[0094] The polishing composition of the present invention (polishing composition for fluorophosphate glass) can be suitably used for polishing fluorophosphate glass used in the lenses of digital cameras or the camera parts built into smartphones.
Claims
1. Silica and A water-soluble polymer compound, an acid and / or a salt thereof; Water and Contains The water-soluble polymer compound is A polymer having structural units derived from a polysaccharide and / or an unsaturated amide, An abrasive composition for fluorophosphate glass, having a pH (25° C.) value in the range of 1.0 to 9.
0.
2. The silica is Colloidal silica, The average particle size (D50) is 2. The abrasive composition for fluorophosphates glass according to claim 1, wherein the particle size is in the range of 10 nm to 200 nm.
3. The acid and / or its salt is 3. The abrasive composition for fluorophosphates glass according to claim 1, which is an inorganic acid and / or a salt thereof.
4. The acid and / or its salt is 3. The abrasive composition for fluorophosphates glass according to claim 1, which is an organic acid and / or a salt thereof.
5. The polymer having a structural unit derived from an unsaturated amide is A structural unit derived from (meth)acrylamide and / or N-substituted (meth)acrylamide; A structural unit derived from (meth)acrylic acid and / or a salt thereof; Contains The abrasive composition for fluorophosphates glass according to claim 1 .
6. The inorganic acid and / or its salt is 4. The abrasive composition for fluorophosphates glass according to claim 3, which is a phosphorus-containing inorganic acid and / or a salt thereof.
7. The organic acid and / or its salt is 5. The abrasive composition for fluorophosphates glass according to claim 4, which is a chelating compound.
8. The chelating compound is 8. The polishing composition for fluorophosphate glass according to claim 7, which is at least one selected from the group consisting of dicarboxylic acids and / or their salts, tricarboxylic acids and / or their salts, polyaminocarboxylic acid compounds, and phosphonic acid compounds.
9. A polishing method using an abrasive composition for fluorophosphates glass, comprising polishing fluorophosphates glass using the abrasive composition for fluorophosphates glass described in any one of claims 1 to 8.
Citation Information
Patent Citations
JP141737A
Production of glass product and filter
JP1998330132A
Method for manufacturing glass optical element
JP2005213091A
Method for polishing a phosphate glass or a fluorophosphate glass substrate
WO2017102826A1